Antinociceptive and Anti-inflammatory Effects of Combined Administration of a-Tocopherol and Morphine in Acetic Acid Induced Writhing Test - Habib, Tamanna; Begum, Shelina; Ali, Taskina; Imtiaz, Masud; Masood, Shahriar (Anwer Khan Modern Medical College Journal, 2017)
Background: Morphine represents the front line therapy for the clinical management of acute and chronic pain but has a number of side effects. So, to minimize the side effect of this tradition analgesic, this study is aimed to explore that combination of morphine and a-tocopherol (?T) are better analgesic as well as anti-inflammatory effect than that of morphine alone. Objective: to assess the effects of combination of morphine with a-tocopherol against nociceptive and inflammatory pain. Methods: This prospective experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January 2013 to December 2013. For this purpose, 15 male Long Evans rats were studied. On the basis of vitamin and drug administrations, the rats were divided into three (3) groups (5 rats in each). Control group received normal saline, one experimental group received morphine sulphate (MS) at a dose of 3 mg/kg body weight and another experimental group received combination of DS with ?T at a dose of 3 mg/kg body weight and 500 mg/kg body weight, respectively. All the groups received single dose and equal volume (1 ml) through intraperitoneal route 1 hour before the test. Just one hour after administrations, they were subjected to acetic acid induced writhing test . The data were statistically analyzed by ANOVA followed by Bonferroni Post Hoc test. Results: combined administration of MS and ?T significantly lowered (p 0.05) the variables for visceral nociceptive pain and inflammatory pain than individual administration of MS. Conclusion: from this study it may be concluded that combined administration of morphine sulphate and a-tocopherol were more effective in lowering the nociceptive and inflammatory pain than individual administration of morphine. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 20-24